Analisis Pengaruh ROA, ROE, Dan DER Terhadap Return Saham (Literature Review Manajemen Keuangan Perusahaan) - Veronika Dora Wesso, Maria; John EHJ. FoEh; Jhonni Sinaga (Jurnal Ilmu Multidisiplin, 2022)
In a research or scientific article, previous research or relevant research is critical. Previous or relevant research contributes to the theory and phenomena of the relationship or influence between variables. This article examines the Influence of Competence, ROA, ROE, and DER on Stock Returns Literature Review of the Company's Financial Management. The goal of this article is to develop a hypothesis about the influence of variables that will be used in future research. The findings of this research library are as follows: 1) ROA has a significant and positive impact on stock return. 2) ROE has a significant and positive impact on stock return. 3) DER has a positive and statistically significant impact on stockreturns. 4) ROA, ROE, and DER have a positive.